Self-sustaining processes at all scales in wall-boundedturbulent shear flows - Cossu,C; Hwang,Y (Royal Society of London. Philosophical Transactions A. Mathematical, Physical and Engineering Sciences, 2017)
We collect and discuss the results of our recentstudies which show evidence of the existence ofa whole family of self-sustaining motions in wallboundedturbulent shear flows with scales rangingfrom those of buffer-layer streaks to those of largescaleand very-large-scale motions in the outer layer.The statistical and dynamical features of this familyof self-sustaining motions, which are associated withstreaks and quasi-streamwise vortices, are consistentwith those of Townsend’s attached eddies. Motionsat each relevant scale are able to sustain themselvesin the absence of forcing from larger- or smaller-scalemotions by extracting energy from the mean flow viaa coherent lift-up effect. The coherent self-sustainingprocess is embedded in a set of invariant solutions ofthe filtered Navier-Stokes equations which take intofull account the Reynolds stresses associated with theresidual smaller-scale motions.